2021
DOI: 10.1111/1467-8268.12509
|View full text |Cite
|
Sign up to set email alerts
|

Effets Potentiels de Court‐terme de la Pandémie de la COVID‐19 sur la Pauvreté dans les Pays de l'Union Economique et Monétaire Ouest Africaine (UEMOA)

Abstract: Résumé Les conséquences socio‐économiques de la crise sanitaire liée à la COVID‐19 ont montré la nécessité de s'interroger sur les effets de cette crise sur les objectifs de développement comme la réduction de la pauvreté afin d'apporter aux décideurs les informations nécessaires pour la mise en œuvre des politiques efficaces. Dans cet article, nous apportons notre contribution à la littérature récente qui traite des effets de la COVID‐19 sur la pauvreté dans l'UEMOA. Nous avons estimé les effets po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
2
0
1
Order By: Relevance
“…Thus presented, the model may suffer from endogeneity problems. Indeed, studies have shown that COVID-19 has an effect on poverty [ 28 , 30 ]. Therefore, there is an endogeneity problem driven by reverse causality.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus presented, the model may suffer from endogeneity problems. Indeed, studies have shown that COVID-19 has an effect on poverty [ 28 , 30 ]. Therefore, there is an endogeneity problem driven by reverse causality.…”
Section: Methodsmentioning
confidence: 99%
“…These results are also supported by the work of [ 27 ] in the case of the Bay Area (San Francisco). In the case of the West African Economic and Monetary Union (WAEMU), [ 28 ] show, using three scenarios of household income reduction (5%, 10% and 25%), that the incidence of poverty could increase in these countries. More recently, [ 29 ] in the case of Mozambique show that the pandemic increased poverty from 4.3 to 9.9%.…”
Section: Introductionmentioning
confidence: 99%
“…Elles sont par conséquent frappées de façon disproportionnée par toute modification des disponibilités en ressources naturelles, mais elles sont aussi idéalement placées pour servir d'agents de changement dans la gestion des ressources naturelles (Fonds des Nations Unies pour l'Alimentation et l'Agriculture, 2017). La littérature empirique sur les déterminants de la participation des pays en développement et notamment africains dans les CVM est récente de même que celle mettant en lumière les effets sociaux économiques et environnementaux (Okah Efogo et al, 2022; Wonyra et al, 2021).…”
Section: Introductionunclassified